2015
DOI: 10.1002/oby.21083
|View full text |Cite
|
Sign up to set email alerts
|

GPRC6a is not required for the effects of a high‐protein diet on body weight in mice

Abstract: ObjectiveThe G-protein coupled receptor family C group 6 member A (GPRC6A) is activated by proteinogenic amino acids and may sense amino acids in the gastrointestinal tract and the brain. The study investigated whether GPRC6A was necessary for the effects of low- and high-protein diets on body weight and food intake in mice.MethodsThe role of GPRC6A in mediating the effects of a low-protein diet on body weight was investigated in GPRC6a knockout (GPRC6a-KO) and wild-type (WT) mice fed a control diet (18% prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Several oligopeptide/AA‐TASRs were expressed in the human mucosa of the proximal gut, but expression of GPRC6A could not be demonstrated even after testing more than 13 different primers. A study in GPRC6A −/− mice showed no crucial role for GPRC6A in protein‐induced satiety and BW loss . Although the highest expression levels of AA‐TASR, with the exception of TAS1R1, were found in the SI, their expression in the stomach argues against the idea that nutrient sensing is limited to the SI .…”
Section: Discussionmentioning
confidence: 99%
“…Several oligopeptide/AA‐TASRs were expressed in the human mucosa of the proximal gut, but expression of GPRC6A could not be demonstrated even after testing more than 13 different primers. A study in GPRC6A −/− mice showed no crucial role for GPRC6A in protein‐induced satiety and BW loss . Although the highest expression levels of AA‐TASR, with the exception of TAS1R1, were found in the SI, their expression in the stomach argues against the idea that nutrient sensing is limited to the SI .…”
Section: Discussionmentioning
confidence: 99%
“…Because of a lack of potent and selective ligands, these suggested functions have mainly been investigated by phenotyping of knock-out mice where the gene function has been destroyed by deletion of exon 6 (Bräuner-Osborne group (17)), exon 2 (Quarles (18) and Karsenty (14) groups), or the full gene (Murphy (19) and Bräuner-Osborne groups (20)). Under normal physiological conditions, these mouse strains have shown very different phenotypes.…”
mentioning
confidence: 99%
“…They did not suffer from increased body fat mass, insulin resistance or glucose intolerance in contrast to the exon II model . The full locus GPRC6A KO mouse has been reported to have normal basal glucose levels, normal response to a glucose tolerance test, no differences in insulin sensitivity or body composition, which is in accordance with the phenotype of the exon VI KO model . Additionally, the full locus GPRC6A KO mice displayed no susceptibility differences in developing dysmetabolism compared to WT in response to a high‐dose glucocorticoid treatment .…”
Section: Suggested Physiological Functions Of Gprc6amentioning
confidence: 63%
“…The Murphy group demonstrated that GPRC6A was not required for the effects of low‐ or high‐protein diets on energy homoeostasis. The full locus KO mice displayed normal food intake and body‐weight when compared to WTs after 9 and 35 days . It remains unknown why the GPRC6A KO mice are more susceptible to high‐fat diet‐induced obesity, while they display normal responses to high‐protein diets, but as mentioned above stress from single housing in a new environment could be a trigger.…”
Section: Suggested Physiological Functions Of Gprc6amentioning
confidence: 95%
See 1 more Smart Citation